Real-time optical biopsy of colon polyps with narrow band imaging in community practice does not yet meet key thresholds for clinical decisions - Ladabaum, Uri; Fioritto, Ann; Mitani, Aya; Desai, Manisha; Kim, Jane P; Rex, Douglas K; Imperiale, Thomas; Gunaratnam, Naresh (Gastroenterology (New York, N.Y. 1943), 2013)
Accurate optical analysis of colorectal polyps (optical biopsy) could prevent unnecessary polypectomies or allow a "resect and discard" strategy with surveillance intervals determined based on the results of the optical biopsy; this could be less expensive than histopathologic analysis of polyps. We prospectively evaluated real-time optical biopsy analysis of polyps with narrow band imaging (NBI) by community-based gastroenterologists. We first analyzed a computerized module to train gastroenterologists (N = 13) in optical biopsy skills using photographs of polyps. Then we evaluated a practice-based learning program for these gastroenterologists (n = 12) that included real-time optical analysis of polyps in vivo, comparison of optical biopsy predictions to histopathologic analysis, and ongoing feedback on performance. Twelve of 13 subjects identified adenomas with >90% accuracy at the end of the computer study, and 3 of 12 subjects did so with accuracy ≥90% in the in vivo study. Learning curves showed considerable variation among batches of polyps. For diminutive rectosigmoid polyps assessed with high confidence at the end of the study, adenomas were identified with mean (95% confidence interval [CI]) accuracy, sensitivity, specificity, and negative predictive values of 81% (73%-89%), 85% (74%-96%), 78% (66%-92%), and 91% (86%-97%), respectively. The adjusted odds ratio for high confidence as a predictor of accuracy was 1.8 (95% CI, 1.3-2.5). The agreement between surveillance recommendations informed by high-confidence NBI analysis of diminutive polyps and results from histopathologic analysis of all polyps was 80% (95% CI, 77%-82%). In an evaluation of real-time optical biopsy analysis of polyps with NBI, only 25% of gastroenterologists assessed polyps with ≥90% accuracy. The negative predictive value for identification of adenomas, but not the surveillance interval agreement, met the American Society for Gastrointestinal Endoscopy-recommended thresholds for optical biopsy. Better results in community practice must be achieved before NBI-based optical biopsy methods can be used routinely to evaluate polyps; ClinicalTrials.gov number, NCT01638091.